Use of Social Media in Uncovering Information Services for People with Disabilities in China - Wang, Wenke; Wu, Yen-Chun Jim; Yuan, Chih-Hung; Xiong, Hongxia; Liu, Wan-Ju (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The tangible and intangible needs of people with disabilities have been neglected in research agendas over the past decades, particularly in China. Bringing more benefits to people with disabilities and combining information delivery with Internet technology to improve their quality of life is impossible if their special needs are ignored. This study employed the crowdsourcing through social media method to investigate information needs of people who are disabled. The results indicate that using the popular social media platforms WeChat and QQ can be an effective means of reaching out to this group. Information needs can be mainly divided into internal and external needs. Leisure, tourism, and entertainment as well as assistive devices are major internal information needs, whereas work, entrepreneurship, and living services are the main external information needs.